Anomalous third head of biceps brachii muscle and its variant insertion compresses surrounding neurovascular structure: a rare case report - Zar, Chi T; Ahmad Ruzain S; Mohammad Johari I; Syed Baharom Syed Ahmad Fuad (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Biceps brachii (BB) is one of the muscles which are subjected to many variations. Recently, there is a lot of information about variations in origin but also some cases are reported on variations in insertion of BB. Presented herein was a case of BB muscle having both variant origin and insertion in the same muscle. The variant origin of BB was long and large at its third head (10.2 cm width and 4.9 cm breadth) which arises from mid-shaft of the humerus. More significantly, the medial portion of the head covers and conceals the lower portion of median nerve and brachial artery as an arch which continues medially to be inserted to the medial epicondyle of the humerus. We discuss in this report, the possible mechanism for neurovascular compression by this abnormal third head of BB muscle and the variation of BB from its origin and insertion. Understanding these variations is highly significant in surgical procedures around elbow joint and upper arm and it also pave the way for the differential diagnosis in nerve entrapment syndrome.